Generation of trust using social networking sites: a comparative analysis of online apparel brands across social media platforms. (17th May 2019) - Sharma, Radhika; Alavi, Shirin; Ahuja, Vandana
The proliferation of social media users has generated hype among marketers to include social media marketing as an integral part of their marketing strategy. Social media marketing has become an important marketing tool which helps create brand awareness, helps build and retain consumer relationships, and increase consumer engagement. The objective of this article is to highlight the importance of social media sites as trust-generating platforms among consumers. This manuscript studies the online content generation strategies of five apparel brands and traces the impact of creation of content across Facebook, Twitter and Instagram. A multiple linear regression analysis is conducted on the data collected using a social media analytics tool. For the regression analysis, the independent variables are number of posts, comments and reactions, while trust is kept as a dependent variable. The results of this study indicated a positive relationship between trust and number of posts, comments, and reactions across all three social networking sites (SNSs). In terms of building trust, Facebook is on top among the three SNSs. The article offers managerial insights regarding usage of SNSs for building trust and consumer engagement.